2019
DOI: 10.1016/j.apsb.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Emodin alleviates cardiac fibrosis by suppressing activation of cardiac fibroblasts via upregulating metastasis associated protein 3

Abstract: Excess activation of cardiac fibroblasts inevitably induces cardiac fibrosis. Emodin has been used as a natural medicine against several chronic diseases. The objective of this study is to determine the effects of emodin on cardiac fibrosis and the underlying molecular mechanisms. Intragastric administration of emodin markedly decreased left ventricular wall thickness in a mouse model of pathological cardiac hypertrophy with excess fibrosis induced by transaortic constriction (TAC) and suppressed activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…In addition, MTA3 also has anti-fibrosis effect (Qin et al, 2015). Xiao et al (2019) further demonstrated that the upregulation of MTA3 may be molecular mechanisms of emodin inhibiting cardiac fibrosis.…”
Section: Mta3mentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, MTA3 also has anti-fibrosis effect (Qin et al, 2015). Xiao et al (2019) further demonstrated that the upregulation of MTA3 may be molecular mechanisms of emodin inhibiting cardiac fibrosis.…”
Section: Mta3mentioning
confidence: 91%
“…Emodin treatment in H9c2 cells with myocarditis Anti-apoptosis (Liu et al, 2013) caspase-3↓, Bcl-2↑ Emodin treatment in BALB/c mice and HEp-2 cells with viral myocarditis (Zhang et al, 2019) miR-138↑, MLK3↓, p53 and p21↓, cyclin D1↑, caspase-3 and caspase-9↓Sirt1/AKT, and Wnt/b-catenin pathways activated, Emodin treatment in H9c2 cells with myocardial ischemia (Huang et al, 2019) miR-26a↓, survivin↑, caspase-3, and caspase-9↓, JAK1/STAT3 signal activated Emodin treatment in H9c2 cells with myocardial ischemia (Ye et al, 2019) GSDMD-N↓, IL-1b↓, TLR4/MyD88/NF-kB/NLRP3 inhibited Emodin treatment in Sprague-Dawley rats cardiomyocytes with ischemia/reperfusion injury Anti-myocardial fibrosis (Xiao et al, 2019) MTA3↑, COL1A2, and a-SMA↓ Emodin treatment in mouse model of pathological cardiac hypertrophy with excess fibrosis Anti-cardiac hypertrophy (Evans et al, 2020) I HDAC and II HDAC activity inhibited, histone acetylation in cardiomyocytes↑, ERK phosphorylation inhibited Emodin treatment in C57BL/6 mice with cardiac hypertrophy (transverse aortic constriction-induced) and fibrosis (AngII-induced) (Gao et al, 2020) SIRT3↑, modulation of mitochondrial SIRT3 and its downstream signaling pathway…”
Section: References Finding Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…1D , the mRNA expression levels of the fibrotic markers, Col1α1, Col3α1, Ctgf and Fn , were notably upregulated in response to miR-375 inhibition. Increased expression levels of α-SMA and periostin in response to TGF-β are known to be hallmarks of myofibroblast transdifferentiation ( 41 ). Consistently, miR-375 inhibition was observed to exacerbate TGF-β-induced upregulation of α-SMA and periostin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It also inhibits monolayer growth and anchorage-independent growth of androgen refractory prostate cancer PC3 cells by targeting the mTOR complex II [39]. More importantly, aloe-emodin has shown potential to treat hepatitis B viral infection [40], a condition that induces liver fibrosis, and to alleviate cardiac fibrosis via suppression of cardiac fibroblast activation by metastasis-associated protein 3 upregulation [41]. Functionally, acacetin has been reported to regulate the reciprocal differentiation of T helper 17 and regulatory T cells as well as the symptoms of collagen-induced arthritis in mice [42].…”
Section: Discussionmentioning
confidence: 99%